Depoliticising Migration - Pécoud, A. author. aut Link
X, 156 p.
Keywords: Migration has become, since the nineties, the subject of growing international discussion and cooperation. By critically analyzing the reports produced by international organisations on migration, this book sheds light on the way these actors frame migration and develop their recommendations on how it should be governed.